Udviklingstendenser i orddannelsen i teknisk fransk i informatikterminologisk belysning - Møller, Bernt (HERMES - Journal of Language and Communication in Business, 1989)
This article outlines current trends in the word formation of French technical LSP. First, a brief review of a fairly traditional, exemplified word formation taxonomy is given also showing the multiplicity of informatique word formation models. The article goes on to survey recent studies in the terminology of information technology. Observations in these studies and in studies in general technical terminologies suggest an increasing trend in the word formation of technical LSP towards a large variety of (combinations of) traditional models, often coupled with brachygraphical techniques; the LSP of informatique further contains a high frequency of semantic neologisms. Finally, perspectivating questions are raised.